Legal Certainty of Performers in Royalty Distribution Disputes Based on the Regulation of the Minister of Law Number 27 of 2025 Concerning Management Implementing Regulations - Inda Nurdahniar; Wiwit Juliana Sari (Rechtsvinding, 2026)
Laws and regulations in Indonesia not only provide legal protection for Creators, but also Related Rights, one of which is Performance Actors. But in practice, the Creator sues the performer for the distribution of royalties, while the event organizer often escapes responsibility. It looks problematic, on the one hand the Creator is given the exclusive right to prohibit or allow anyone to use his creation. Meanwhile, on the other hand, the performers contribute to the creations created by the Creator, so that they sell well in Indonesia. Meanwhile, if there is a problem, the Creator can prohibit the Performance Actor at any time from using his creation, even though this situation can hinder the Performance Actor from obtaining Economic Rights. The purpose of this research is to analyze legal certainty for Performers regarding the distribution of royalties in the era of the birth of Permenkum 27/2025. The research method in this article is normative juridical with a qualitative approach to laws and regulations and royalty-related problems that are rampant. The results of this study explain that based on Permenkum 27/2025, Performance Actors are not obliged to pay royalties, but this is charged to the event organizer. Where the royalty distribution mechanism is carried out through LMKN through a SILM system (distribution of royalties from LMK to Creators and Related Rights) and INSPIRATION (distribution of royalties from users to LMKN). With this legal certainty, the Plaintiff is no longer the party who is held responsible for the distribution of royalties. It is hoped that there will be no more creators who prohibit performers from performing their songs due to the uncertainty of royalty payments because it will disrupt the ecosystem of a work or even tarnish the reputation/good name of the performers.